Analysis of Labor Productivity on Lightweight Brick Masonry Work using The Work Sampling Method - Fadillah, Naufal Luthfi; Putra, I Nyoman Dita Pahang (Composite: Journal of Civil Engineering, 2024)
One of the important elements in the construction process is lightweight brick work. Labor productivity in this work is very influential on the progress of the construction project as a whole. One method that can be applied to analyze labor productivity is work sampling, which is an observation method used to measure and analyze the productivity of workers or activities at a certain time. This study aims to investigate and analyze labor productivity of lightweight brick work labor. The work sampling method was chosen to analyze the productivity and quantity of labor in lightweight brick work on the Bekasi Mixed Use Development Pakuwon Residence project. Based on the analysis and discussion during the 10-day observation period, 8 lightweight brick masonry workers completed work with a total area of 658.480 m2 and obtained a productivity value of 52,730 m2/day. In addition, from the results of field observations, the level of worker adjustment factors and allowances can still be increased, with the hope that this increase will significantly increase worker productivity in terms of time, quality, and quantity.